Investigating the nexus between authentic leadership, employees' green creativity, and psychological environment: evidence from emerging economy - Rehman, Fazal ur; Zeb, Ali (Springer, 2023)
Employees' green creativity is the basic input to organizational innovation capabilities, the prime focus of practitioners to stay competitive, and a mean to solve the society's sustainable issues in dynamic markets. Hence, this study aims to evaluate the nexus between authentic leadership, psychological environment, and employees' green creativity based on the theoretical lenses of social identity and social exchange theories that have rare application in these domains. Data were collected through questionnaires from 367 operational staff members of different technical training centers of renewable energy projects in Rawalpindi and Islamabad regions at Pakistan. The findings reveal that authentic leadership is a significant precursor of employee's green creativity and self-efficacy. In addition, self-efficacy mediates while the environment of trust and safety has non-mediating role in the relationship between authentic leadership and employee's green creativity. This work brings attention to the initiatives in technical training centers for renewable energy projects and contributes to the field of employees' green creativity in the context of authentic leadership and psychological environment based on the philosophy of social identity and social exchange theories.
Zkoumání spojitosti mezi autentickým vedením, zelenou kreativitou zaměstnanců a psychologickým prostředím: důkazy z rozvíjející se ekonomiky
Keywords: Authentic leadership; Psychological environment; Employee's green creativity; Autentické vedení; Psychologické prostředí; Zelená kreativita zaměstnanců